Finite‐state model predictive power control of three‐phase bidirectional AC/DC converter under unbalanced grid faults with current harmonic reduction and power compensation. Issue 2 (9th January 2018) - Jin, Nan; Guo, Leilei; Gan, Chun; Hu, Shiyang; Dou, Zhifeng
Abstract : Under unbalanced grid fault conditions, the current harmonic contents of a three‐phase bidirectional AC/DC converter increase significantly and twice grid‐frequency ripples exist in both active power and reactive power, which influence the output power quality of the converter. Compared with the conventional finite‐state model predictive direct power control (MPDPC), the MPDPC with power compensation (MPDPC‐PC) method is proposed for the three‐phase bidirectional AC/DC power converter to reduce harmonic currents and output power ripples without extraction of complex positive/negative sequences from the grid voltage/current and phase‐locked loop. The power compensation values are expressed by grid voltages and their quadrature signals that lag 90 electrical degrees in the αβ stationary coordinates system. MPDPC‐PC exhibits better performance by reducing the harmonic contents of grid currents and eliminating active power or reactive power ripples of the three‐phase bidirectional AC/DC converter with flexible reactive power compensation capability. Compared with the MPDPC and linear current control schemes, experimental results confirm the effectiveness of the designed method under unbalanced grid conditions.